Induction of Potent and Long-Lived Antibody and Cellular Immune Responses in the Genitorectal Mucosa Could be the Critical Determinant of HIV Vaccine Efficacy - Chanzu, Nadia; Ondondo, Beatrice (Frontiers in Immunology, 2014)
The field of HIV prevention has indeed progressed in leaps and bounds, but with major limitations of the current prevention and treatment options, the world remains desperate for an HIV vaccine. Sadly, this continues to be elusive as more than 30 years since its discovery there is no licensed HIV vaccine. Research aiming to define immunological biomarkers to accurately predict vaccine efficacy have focussed mainly on systemic immune responses, and as such, studies defining correlates of protection in the genito-rectal mucosae, the primary target site for HIV entry and seeding are sparse. Clearly, difficulties in sampling and analysis of mucosal specimens, as well as their limited size have been a major deterrent in characterizing the type (mucosal antibodies, cytokines, chemokines or CTL), threshold (magnitude, depth and breadth) and viral inhibitory capacity of HIV-1 specific immune responses in the genito-rectal mucosae, where they are needed to immediately block HIV acquisition and arrest subsequent virus dissemination. Nevertheless, a few studies document the existence of HIV-specific immune responses in the genito-rectal mucosae of HIV-infected aviremic and viremic controllers, as well as in highly exposed persistently seronegative (HEPS) individuals with natural resistance to HIV-1. Some of these responses strongly correlate with protection from HIV acquisition and/or disease progression, thus providing significant clues of the ideal components of an efficacious HIV vaccine. In this article, we provide an overview of the key features of protective immune responses found in HEPS, elite and viremic controllers and discuss how these can be achieved through mucosal immunization. Inevitably, HIV vaccine development research will have to consider strategies which elicit potent antibody and cellular immune responses within the genito-rectal mucosae or induction of systemic immune cells with an inherent potential to home and persist at mucosal sites of HIV entry.